2018
DOI: 10.1186/s12889-018-6226-7
|View full text |Cite
|
Sign up to set email alerts
|

Measles vaccination coverage, determinants of delayed vaccination and reasons for non-vaccination among children aged 24–35 months in Zhejiang province, China

Abstract: BackgroundThis study was aimed to assess the coverage of two doses of measles vaccine and identify the determinants of the delayed vaccination.MethodsA cluster survey among 1386 children aged 24–35 months was conducted. Characteristics on demographic and socio-economic and vaccination records was collected. The overall coverage was defined as the proportion of children receiving the first dose of measles vaccination and the second dose of measles vaccination by 24 months of age. The age-appropriate coverage wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
(20 reference statements)
2
17
4
Order By: Relevance
“…This calls for age appropriateness of vaccination to be considered as another indicator of vaccination program performance to ensure timely administration of vaccination for children. In contrast to this, a study done in Zhejiang province of China found a comparably high proportion of age-appropriate measles vaccination [33]. Nonetheless, as the national experience of Italy tells us [34,35], measles elimination, of course to all VPDs elimination, will remain unrealized dream unless the vaccination program is being monitored against its schedule with strong political commitment.…”
Section: Discussionmentioning
confidence: 99%
“…This calls for age appropriateness of vaccination to be considered as another indicator of vaccination program performance to ensure timely administration of vaccination for children. In contrast to this, a study done in Zhejiang province of China found a comparably high proportion of age-appropriate measles vaccination [33]. Nonetheless, as the national experience of Italy tells us [34,35], measles elimination, of course to all VPDs elimination, will remain unrealized dream unless the vaccination program is being monitored against its schedule with strong political commitment.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 Policy-level factors include policies about health and social insurance. 13,14 One focus of this study was to examine rural-urban differences in the incomplete immunization of children. 15 Currently, there are large rural-urban differences in population health and health service utilization in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed vaccination extends the period of the risk of disease for the individual child, but under-vaccination/low coverage is what affects herd immunity. Hence, the current indicator for 2 doses MCV is diphtheria-tetanus-pertussis (DTP3) vaccination coverage level [ 5 ], [ 7 ]. Delayed vaccination weakens herd immunity and increases the probability of outbreaks due to a large gap between the protection from vaccination and the loss of maternal antibodies [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the current indicator for 2 doses MCV is diphtheria-tetanus-pertussis (DTP3) vaccination coverage level [ 5 ], [ 7 ]. Delayed vaccination weakens herd immunity and increases the probability of outbreaks due to a large gap between the protection from vaccination and the loss of maternal antibodies [ 7 ]. Vaccination coverage is an indicator widely used for evaluating the immunisation program [ 7 ].…”
Section: Introductionmentioning
confidence: 99%